Thermally stable and efficient polymer solar cells based on a novel donor-acceptor copolymer. (13th May 2016) - Synooka, O; Eberhardt, K-R; Balko, J; Thurn-Albrecht, T; Gobsch, G; Mitchell, W; Berny, S; Carrasco-Orozco, M; Hoppe, H
Abstract: We report high photovoltaic performance of a novel donor-acceptor (D-A) conjugated polymer poly[2, 6[4, 8-bis(2-ethyl-hexyl)benzo[1, 2-b;4, 5-b′]dithiophene-co-2, 5-thiophene-co-4, 7[5, 6-bis-octyloxy-benzo[1, 2, 5]thiadiazole]-co-2, 5-thiophene] (PBDTTBTZT) in bulk heterojunctions with [6, 6]-phenyl-C71-butyric acid methyl ester (PC70 BM). A power conversion efficiency (PCE) of more than 7% is obtained for optimized charge-extracting electrodes. Upon application of thermal stress via annealing, a superior thermal stability is demonstrated as compared to poly[N-9″-hepta-decanyl-2, 7-carbazole-alt-5, 5-(4′, 7′-di-2-thienyl-2′, 1′, 3′-benzothiadiazole)] (PCDTBT).